El uso de los valores sociales en la comunicación publicitaria: la socialización corporativa - Hellín Ortuño, Pedro A. (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
We present in this paper the results of a socio–semiotic analysis on a large sample of graphical advertising. This analysis tries to know the intensity and the type of the social values used as communication axes in the advertisements.